10 MINUTES EXTENSIVE READING AND ITS EFFECT FOR LEARNERS WRITING AND SPEAKING SKILL - Novi Rahmania Aquariza; Syafi'ul Anam; Pratiwi Retnaningdyah (E-LINK JOURNAL, 2019)
In this article an explanation of what Extensive Reading is delivered. The article starts by delivering the general idea of what Extensive Reading is. Then the possible benefits and also obstacles of it are also delivered as well as the previous study discussed. Then, the origin of writing and spaking skill stated in line with the steps of how to apply the Extensive Reading in the teaching and learning process are also detailed in this article.Key words: Extensive Reading, Writing Skill, Speaking Skill